Sportmedizinische Leistungsdiagnostik im Badminton - Wonisch, M.; Hofmann, P.; Schwaberger, G.; Almer, A.; Golda, M.; Hödl, R.; Klein, W. (Österreichisches Journal für Sportmedizin, 2000)
The aim of this study was to compare a badminton-specific field test based on the Concconi-method with a standard incremental treadmill test under laboratory conditions (n=23).